Numerical Analysis of Hybrid Steel Beams with Trapezoidal Corrugated Web Nonwelded Inclined Folds - Yasir M. Alharthi; Ibrahim A. Sharaky; Ahmed S. Elamary (Advances in Civil Engineering)
Hybrid beams provide the opportunity to implement characterized steel sections by recruiting materials based on yield strength and the type of applied stress. Previous studies demonstrated that steel beams with a trapezoidal corrugated web (SBCWs) were affected by both fatigue cracks initiated along the inclined fold (IF) and the maximal additional stress located in the middle of the IFs. This paper presents a numerical study of hybrid SBCWs and nonwelded IFs. Numerical simulation is presented using the finite element (FE) method with the aid of the ANSYS software package. Three-dimensional FE models were developed considering the nonlinear properties of materials and geometric imperfection and validated using five hybrid specimens that were fabricated and tested experimentally by the authors. The load-deflection behavior and failure mechanism of the numerical results were in good agreement with the experimental results. The comparison of the FE models and the experimental results shows the good capability of the FE model to be used as a base for the parametric study. The parametric study focused on the effect of web thickness, flange thickness, web height, and flange and web steel grades. Furthermore, parametric studies are conducted to investigate the effects of the number and depth of the stiffeners on the behavior of hybrid SBCWs. We concluded that the flange thickness, web thickness, web height, and steel grades of flanges significantly affect the capacity and failure mode of hybrid SBCWs. We also concluded that the flange stiffeners have a significant effect on the overall behavior, toughness, and load capacity of SBCWs. Finally, a new equation is proposed to anticipate the shear capacity of SBCW nonwelded IFs based on the length of the welded horizontal fold.